Selected Aspects of European Integration of the Visegrad Group Countries - Błaszczyk, Maria Celina (Comparative Economic Research. Central and Eastern Europe, 2022)
This paper analyzes the membership of the Visegrad Group countries (the Czech Republic, Poland, Slovakia, and Hungary) in the European Union (EU). It presents the parallel process of fundamental systemic transformation and integration with the EU in the analyzed countries. Their integration path is shown, starting from the association with the European Communities, a transitional period to membership, through adjustments to the requirements related to EU accession and membership. A comparative analysis of the main macroeconomic indicators, trade development, and the inflow of foreign direct investment showed that the adopted measures and the membership of these countries in the EU positively impacted their overall socio‑economic development, in particular in the context of modernizing and restructuring their economies, which ultimately translated into the civilizational leap of the analyzed countries.